Correlation of peripheral pulse wave features and pulse rate variability parameters with hospitalization of COVID-19 patients – the scientific aspect of a tele-pulse oximetry project study design. (14th October 2021) - Kulin, D; Antali, F; Kulin, S; Dozsa, K; Bekassy, S; Miklos, Z
Abstract: Introduction: The Operational Group, leading the fight against COVID-19 in Hungary, has approved a pilot program, in December 2020, to monitor high risk COVID-19 patients in 40 family practices. The main goal of this project is to connect family physicians to their COVID-19 patients through a telemedicine system, in order to ensure patients' security and support for personalized telemedical-care and on-time hospitalization of the patients. 200 special pulse-oximeters were distributed and are continuously rotated among patients with acute phase of infection. Every patient is required to install a smartphone application on their phones to capture and transfer the oxygen saturation (SpO2), heart rate and raw pulse wave data. The peripheral pulse wave is used for calculating more than 30, cardiovascular and autonomic nervous system parameters by a proprietary algorithm. Most of these parameters are well described in the medical literature but not used for decision support in this project. Research question: Do remote pulse wave analysis parameters have a predictive value on hospitalization above SpO2 recordings in COVID-19 patients? Methods: Retrospective observational cohort study. The data analysis will be performed on the pulsewave database collected during the above mentioned project and correlated with endpoints. The parameters are measured with a special pulse oximeter; transferred, stored, processed and calculated by a remote patient monitor platform. The information about primary and secondary endpoints will be collected from the primary care physician of the patient. Study population: Patients with diagnosed SARS-CoV-2 infection who have been monitored with a certain remote patient monitor system between November 2020 and September 2021. Expected number of participants: 100–150 patients. Primary endpoint: Hospitalization due to acute COVID-19 infection Secondary endpoints: Death connected to SARS-CoV-2 infection, presence of long-COVID symptoms during the monitoring period- maximum one month after the start of the infection Expected outcome: According to literature data pulse wave features show correlation with cardiovascular status of the patient, while pulse rate variability parameters can be descriptive of the autonomic nervous system status of the subject. These parameters are described to possibly alter during and after an acute SARS-CoV-2 infection. To our knowledge there was no similar telemedical pulsewave data collection and analysis relation to COVID-19 before. However this is an easy to use methodology to explore more details about the patient's status. In this research we aim to explore these parameter's clinical utility in COVID-19 patients. Results will help to determine if pulse wave analysis and pulse rate variability parameters can be used as indicators of higher risk of hospitalization in COVID-19 patients. FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): E-Med4All Europe Kft., Budapest, Hungary